A Co2+-selective and chirality-sensitive supermolecular metallohydrogel with a nanofiber network skeleton. Issue 12 (7th March 2016) - Wang, Xiaojuan; He, Ting; Yang, Lan; Wu, Huiqiong; Zhang, Rui; Zhang, Zhenzhu; Shen, Rujuan; Xiang, Juan; Zhang, Yi; Wei, Chuanwan
Abstract : This paper introduces a new metallohydrogel precursor that offers a peculiar gelation response to Co 2+ at pH 7–8. Abstract : This paper introduces a new metallohydrogel precursor that offers a peculiar gelation response to Co 2+ at pH 7–8. It is notable that the stability of this metallohydrogel is significantly dependent on its enantiomeric purity. In addition to the expected multi-stimuli responsive properties, including thixotropy, as well as re-assembly properties on adding HCl, this metallohydrogel possesses excellent self-healing behavior, which is uncommon in low-molecular-weight gelators. Electron microscopy (EM) studies revealed that the cryodried remains of this gel presented as well an organized three dimensional (3D) network of fibrils. This interesting metallohydrogel shows potential for developing new soft materials with drug delivery and catalysis properties.